BUILDING CONFIDENCE AND FLUENCY: STRATEGIES FOR ENCOURAGING ENGLISH SPEAKING IN CLASS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Developing confidence and fluency in speaking is a critical goal for English language learners. However, many students struggle with anxiety, lack of motivation, and insufficient opportunities to practice speaking. This article explores effective strategies that teachers can implement to encourage speaking in class, focusing on methods such as task-based learning, peer collaboration, role-play, and positive reinforcement. These strategies have been shown to build student confidence, reduce speaking anxiety, and improve fluency over time. The article also discusses the importance of creating a supportive classroom environment where students feel comfortable using English freely and without fear of making mistakes.